Role of Technology in Chemistry - Popalzai, Raihana; Nair, Mohammad Mustaf (Journal of Natural Sciences – Kabul University, 2021)
The advent of advanced technology has revolutionized communication and information exchange, allowing people to access the latest developments in any field instantly. Among its many applications, technology's impact on scientific and educational environments is particularly significant. It complements traditional education by addressing academic challenges such as design, implementation, and evaluation, ultimately achieving high-quality scientific goals. Chemistry, like other sciences, has greatly benefited from technological advancements. This study explores the role and application of technology in teaching and learning chemistry. It highlights the benefits of using information technology in educational practices and introduces several systems, such as ISIS/Draw, Chem Tool Box, and Chem Office, demonstrating their utility in chemistry education.